Origin and fate of vascular smooth muscle cells during vascular remodeling and reverse remodeling in pulmonary hypertension - Chu, Xuran; Justus Liebig University Giessen (My University, 2022)
Pulmonary hypertension occurs when the pressure in the blood vessels leading from the heart to the lungs is too high. During pulmonary hypertension, the blood vessels in the lungs develop an increased amount of smooth muscle cells (SMCs) in the wall of the blood vessels. Investigating the origin of the neo-muscularization is crucial to find the potential therapy for PH. Previous studies have shown that pre-existing SMCs primarily a source of newly formed SMC via clonal expansion in PH. Our study used Gli1Cre-ERT2 mice to lineage trace GLI1+ cells in PH during vascular remodel and reverse remodel phase and showed that GLI1+ cells contribute to the neo-muscularization in PH and resolution of PH in the reverse remodelling phase. We also used Gli1Cre-ERT2; iDTRflox line to carry out genetic ablation of GLI1+ cells in mice to investigate the pathological role of GLI1+ cells in PH. Genetic ablation of GLI1+ cells at the beginning of hypoxic injury protects lungs from PH development, confirmed by echocardiography, FACS and IF analysis. Furthermore, IF analysis on PCLS showed that GLI1+ cells contribute to the newly-formed ACTA2+ cells in distal blood vessels through local recruitment and transdifferentiation in hypoxia-induced PH. scRNA-seq on GLI1+ cells obtained from hypoxia-induced PH mice indicates that GLI1+ cell lineage is highly heterogeneous. Among 12 clusters found in the scRNA-seq, we found cluster 9 contains the signature genes of vascular SMCs and the cell in cluster 9 is enriched in hypoxia-induced PH. In conclusion, GLI1+ cell lineage is a source of newly-formed vascular SMCs in PH via local recruitment and transdifferentiation.
Keywords: ddc:610